Prediction and Management of Severe Acute Pancreatitis - Forsmark, Chris E.; Gardner, Timothy B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This volume provides a comprehensive summary of pancreatitis and its complications, with expert recommendations on prediction and management. The text thoughtfully summarizes the current prediction models for severe acute pancreatitis, including laboratory, clinical and imaging parameters, and highlights the relative advantages and disadvantages of several of these models. Evidenced-based guidelines into medical and surgical management of both the hospitalized and discharged patient are described, with recommendations from expert authors pertaining to various clinical situations. The volume also discusses complications of acute pancreatitis and their management, including the use of cutting-edge minimally-invasive therapies. Prediction and Management of Severe Acute Pancreatitis serves as the fundamental source for those interested in and treating this disease, including practicing gastroenterologists, surgeons, radiologists, intensivists, hospitalists and pathologists.
1. Revised Atlanta Classification of Acute Pancreatitis -- 2. Organ Failure and Acute Pancreatitis -- 3. Sterile and Infected Pancreatic Necrosis -- 4. Evolving Definitions of Severe Acute Pancreatitits -- 5. Clinical Predictors -- 6. Imaging Predictors -- 7. Predictive Scoring Systems in Acute Pancreatitis -- 8. Fluid Resuscitation in Acute Pancreatitis -- 9. Antiobiotic Therapy -- 10. Nutrition in Severe Acute Pancreatitis -- 11. Pharmacologic Therapy -- 12. Management of Ductal Leaks -- 13. Endoscopic Management of Severe Gallstone Pancreatitis -- 14. Direct Endoscopic Necrosectomy -- 15. Retroperitoneoscopic Approaches for Infected Necrotizing Pancreatitis -- 16. Surgical Approaches -- 17. Internventions for Nectrotizing Pancreatitis: A Mutlidisciplinary Approach.
Keywords: Gastroenterology .; Surgery; Interventional radiology .; Gastroenterology; General Surgery; Interventional Radiology